Parasites and diet of Serrasalmus maculatus in a hydroelectric reservoir in Brazil - Miguel, Bianca da Silva [UNESP]; Franceschini, Lidiane [UNESP]; Manoel, Letícia de Oliveira [UNESP]; Kliemann, Bruna Caroline Kotz [UNESP]; Delariva, Rosilene Luciana; Ramos, Igor Paiva [UNESP] (FapUNIFESP (SciELO), 2022)
Serrasalmus maculatus is a species of piranha which, despite being abundant in a reservoir environment, has few studies related to its parasitological and diet aspects. Thus, we aimed to document the parasitic fauna and diet of the S. maculatus in a hydroelectric reservoir in Brazil. In addition, we perform two literature reviews for the Neotropical region, recording the parasitic fauna already associated with S. maculatus and the occurrence of parasite genera identified in this study parasitizing Characiformes from other aquatic systems. Thirty-one hosts were collected with gillnets, from August 2014 to September 2016. Serrasalmus maculatus had a piscivorous feeding habit and a low richness parasitic component community, including two taxa of monogeneans, Anacanthorus lepyrophallus and Mymarothecium sp.; no endohelminths were observed. Data from the literature review, together with the findings of the study, showed that S. maculatus in the Neotropical region harbors 25 helminth taxa, with the monogenean being the most prevalent parasitic group and Brazil is the country with the most reports of the parasitic genera. These findings provide information on the relationships between diet, social behavior, and parasitic fauna of S. maculatus and on the patterns of distribution and infection of the observed parasite rates.